Role of portable ultrasound during a short-term medical service trip to rural Guatemala: a collaborative mission of trainees and physicians - Ahmed Elsayes; Scott Rohren; Nadim Islam; Katherine Blair; Alicia Silvestre; Daniela Segura; Theodore Dubinsky (James Cook University, 2021)
Introduction: Access to health care in developing countries is scarce. One solution to this problem has been for doctors from the USA to provide single-visit care through short-term medical service trips. There is interest in using ultrasound imaging as a portable diagnostic tool; however, data describing its usefulness are scarce. Therefore, the goal of this study was to determine the usefulness of portable ultrasound imaging during a medical service trip to rural Guatemala. Methods: A multidisciplinary team of physicians examined patients at a mobile clinic in Antigua, Guatemala. Patients with clinical indications for ultrasound had their suspected diagnoses recorded before ultrasound testing. After imaging, updated diagnoses were recorded and compared with the pre-test suspected diagnoses to determine how often ultrasound results changed the medical management of the patients and to assess the most common indications for ultrasound imaging. Results: During the trip, 205 patients were seen. Of these, 24 (12%) were given ultrasound exams. The results of 13 (54%) exams altered their medical management, and the remaining 11 (46%) exams confirmed the pre-test suspected diagnoses. The most common indications for ultrasound testing were suspected cardiac (11 patients, 46%) and gastrointestinal (8 patients, 33%) diseases. Conclusion: Portable ultrasound imaging improved the medical team's ability to diagnose disease and clinically manage patients in a rural medical service trip. Ultrasound imaging may provide a low-cost solution to the growing demand for care in developing countries.